Elephant numbers in Kafue National Park, Zambia - Guldemond, Robert; Lehman, Emily; Ferreira, Sam; van, Aarde (Pachyderm, 2005)
This article compares aerial survey data from the Kafue NP and surrounding GMAs from 1991 to 2004. This was done in part to check the precision of the counts and in part as a reviews the apparent situation in Zambia which suggests that unlike other southern Afican areas the elepahant population of Zambia is decreasing rather than increasing. The estimated population was over 10000 in 1991 with about half in Kafue NP itself and the rest largely in Mumbwa and Sichifula GMAs, with about 2500, and in Mulobezi with about 1600 and a some in Lunga-Luswich. In a 1996 survey the total population was under 5000 the majority of animals were in Kafue NP with a small number in Mumbwa and Sichifula GMAs. The 2004 survey noted elephant only in Kafue NP itself and the estimated total population was 1555 which was lower tht the 3798 estimation from the 2001 counts which also observed animals only in Kafue NP.